2021
DOI: 10.1039/d1na00077b
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring silver nanoclusters via doping: advances and opportunities

Abstract: Atomically precise noble metal nanoclusters (espically Au and Ag) have been pursued due to their fascinating molecular-like properties. In spite of the significant progress of Au nanoclusters (NCs), the structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…These considerations are even more dramatic when two different metal precursors are engaged, rendering the rational preparation of heterobimetallic entities extremely challenging. Postmodification strategies, such as doping of monometallic clusters with heterometal atoms, or rearrangement of two independently synthesized monometallic clusters, are emerging approaches that have attracted substantial interest recently, but so far are limited to thiolate or carbonyl metal clusters. Lability phenomena and metal exchange strategies in polyhydride metal clusters are much less investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations are even more dramatic when two different metal precursors are engaged, rendering the rational preparation of heterobimetallic entities extremely challenging. Postmodification strategies, such as doping of monometallic clusters with heterometal atoms, or rearrangement of two independently synthesized monometallic clusters, are emerging approaches that have attracted substantial interest recently, but so far are limited to thiolate or carbonyl metal clusters. Lability phenomena and metal exchange strategies in polyhydride metal clusters are much less investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…11 The use of dithiolated molecules allows for exploring different staple motifs (as compared to those obtained with single thiolated molecules) and therefore adds some versatility to doping strategies. Several experimental studies showed that doping of silver nanoclusters with dithiolated molecules with heteroatoms present enhanced catalytic activity, photoluminescence (PL) and stability, and due to synergistic effects, 27 Van der Linden et al demonstrated such enhanced PL and stability by doping Ag 29 nanoclusters capped with lipoic acid with Au. 28 On the other hand, Bootharaju et al were able to perform doping of Ag 29 clusters with a single Pt atom, i.e., leading to enhanced excited-state lifetime and PL intensity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[70][71][72][73] Heteroatomdoped metal NCs are highly desirable to get some clues about the effect of doping on the electronic structure and catalytic properties. [74][75][76] Furthermore, due to the ultrasmall size of NCs, the structure and physicochemical properties of NCs are highly sensitive to their composition/structure. Even the introduction, removal, or replacement of a metal atom will cause dramatic changes in its properties.…”
Section: Doping/alloying Effectmentioning
confidence: 99%